The Italian agricultural simple partnership (società semplice agricola): an agricultural enterprise, a non-commercial legal form and its registration in the Business Register - Tedioli, Francesco (Przegląd Prawa Rolnego, 2026)
This article examines the Italian società semplice agricola as a distinctive model of non-commercial partnership for the collective exercise of agricultural enterprise. Its civil-law flexibility makes it particularly suitable for family farms, intergenerational holdings and land-based agricultural undertakings. However, this flexibility becomes problematic once the partnership is registered in the special agricultural section of the Business Register and its registered position is used by third parties, public authorities and sectoral benefit schemes. The article analyses the tension between internal contractual autonomy and public reliability, focusing on the legal nature of the agricultural simple partnership, its registration, connected activities under Article 2135 of the Italian Civil Code, subjective and objective changes, professional agricultural status and the absence of a coherent mechanism for requalification or cancellation. It argues that the società semplice agricola remains a valuable instrument for preserving the non-commercial character of collective farming, but that its effectiveness depends on a publicity regime capable of accurately reflecting the enterprise’s legal and economic reality.